2021
DOI: 10.21608/ejhm.2021.162850
|View full text |Cite
|
Sign up to set email alerts
|

Study of Subclinical Atherosclerosis in Patients with Type 2 Diabetes Mellitus

Abstract: Background: Patients with type 2 diabetes mellitus (T2DM) are at increased risk of atherosclerosis. The early recognition of atherosclerosis at its subclinical stages can slow or prevent progression to atherosclerotic diseases, including coronary artery disease, cerebrovascular disease, and peripheral arterial disease. Objective: Identification of the relationship between T2DM and subclinical atherosclerosis and to explore factors that can be associated with a high risk of subclinical atherosclerosis. Patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…A recent literature found that individuals with uncontrolled diabetes had thicker CIMT than their nondiabetic and well controlled diabetic counterparts, but there was no correlation between 2 h-PPG and CIMT values, similar to our observation. [18] These findings suggest the superior nature of intermediate hyperglycemia in diagnosing early atherosclerosis. Furthermore, Tenjin et al .…”
Section: Discussionmentioning
confidence: 99%
“…A recent literature found that individuals with uncontrolled diabetes had thicker CIMT than their nondiabetic and well controlled diabetic counterparts, but there was no correlation between 2 h-PPG and CIMT values, similar to our observation. [18] These findings suggest the superior nature of intermediate hyperglycemia in diagnosing early atherosclerosis. Furthermore, Tenjin et al .…”
Section: Discussionmentioning
confidence: 99%